2017
DOI: 10.1016/j.gdata.2017.03.013
|View full text |Cite
|
Sign up to set email alerts
|

A metagenomic approach to decipher the indigenous microbial communities of arsenic contaminated groundwater of Assam

Abstract: Metagenomic approach was used to understand the structural and functional diversity present in arsenic contaminated groundwater of the Ganges Brahmaputra Delta aquifer system. A metagene dataset (coded as TTGW1) of 89,171 sequences (totaling 125,449,864 base pairs) with an average length of 1406 bps was annotated. About 74,478 sequences containing 101,948 predicted protein coding regions passed the quality control. Taxonomical classification revealed abundance of bacteria that accounted for 98.3% of the microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 48 publications
3
29
0
Order By: Relevance
“…This method has used for the identification of very rare populations which is present in very low abundance that may necessary for the functional diversity and ecosystem stability (Sogin et al ., 2006; Staley et al ., 2013). Several bacterial communities from different environmental samples like marine waters (Brown et al ., 2009), soils (Jones et al ., 2009), wastewater (Sanapareddy et al ., 2009), contaminated water (Das et al ., 2017) and several human microbiomes were successfully characterized (Staley et al ., 2013; Sanapareddy et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This method has used for the identification of very rare populations which is present in very low abundance that may necessary for the functional diversity and ecosystem stability (Sogin et al ., 2006; Staley et al ., 2013). Several bacterial communities from different environmental samples like marine waters (Brown et al ., 2009), soils (Jones et al ., 2009), wastewater (Sanapareddy et al ., 2009), contaminated water (Das et al ., 2017) and several human microbiomes were successfully characterized (Staley et al ., 2013; Sanapareddy et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that Burkholderia can enhance arsenic toxicity by reducing methyl-arsenate compounds to toxic methyl-arsenite [46]. Interestingly, Burkholderia was also among the most prominent genus in recent metagenomic surveys from other arsenic-contaminated regions located in India [47] and Bangladesh [48].…”
Section: Diversity Of Betaproteobacteria In the Bdp Aquifersmentioning
confidence: 99%
“…ABC-type Fe 3+ -siderophore transport system, Ferric hydroxamate ABC transporter (EC 3.A.1.14.3), Isochorismate synthase (EC 5.4.4.2) of siderophore biosynthesis, Siderophore biosynthesis protein, Siderophore synthetase component and TonB-dependent proteins. Different siderophores linked gene sequences that resembled pyoverdine (generally produced by the members of the family Pseudomonaceae, i.e., Azotobacter, Azomonas, Pseudomonas, and Rhizobacter) [75] , achromobactin (siderophore produced by Pseudomonas syringe) [76]; yersiniabactin (siderophore of the pathogenic bacteria Yersinia pestis, Yersinia pseudotuberculosis, and Yersinina enterocolitica) [77]; bacillibactin (siderophore synthesized by the genus Bacillus) [78]; enterobactin and pyochelin (siderophore synthesized by Pseudomonas aeruginosa) [79,80] were traced in the dataset. We speculate that the dominant presence of microbial communities linked with the efficient iron acquisition functions is supposed to make them enable to enhance iron bioavailability in the rhizosphere of kodo plants.…”
Section: Iron Acquisition and Metabolismmentioning
confidence: 99%